2022
DOI: 10.3390/ph15030350
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Inflammatory Effect of Humulus lupulus Extract In Vivo Depends on the Galenic System of the Topical Formulation

Abstract: We demonstrated the anti-inflammatory and anti-oxidative effects of Humulus lupulus (HL) extract on solar simulator-irradiated primary human keratinocytes (PHKs) by analyzing ERK and p38 MAPK phosphorylation and production of IL-6 and IL-8. The anti-inflammatory effect of topically applied HL was further tested in vivo on human skin. To this end, we developed an oil-in-water (O/W) and a water-in-oil (W/O) cream with a lipid content of 40%. The anti-inflammatory effect of 1% HL extract incorporated in these two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Hop extract has been found to possess various pharmacological properties. For instance, it exhibits antitumor and anti-inflammatory effects, as evidenced by previous studies [322]. Moreover, the extract has been reported to possess antibacterial, anticollagenase, and antioxidant activity [323].…”
Section: Humulus Lupulus L Hemp Family -Cannabaceaementioning
confidence: 63%
See 1 more Smart Citation
“…Hop extract has been found to possess various pharmacological properties. For instance, it exhibits antitumor and anti-inflammatory effects, as evidenced by previous studies [322]. Moreover, the extract has been reported to possess antibacterial, anticollagenase, and antioxidant activity [323].…”
Section: Humulus Lupulus L Hemp Family -Cannabaceaementioning
confidence: 63%
“…In dermatology, extracts of H. lupulus have been employed as an antipsoriatic medication [322]. Furthermore, they are used in the management of inflammatory skin disorders in adolescents, and hop cones are taken orally to address baldness, furunculosis, lichen, and scrofula [318,323].…”
Section: Humulus Lupulus L Hemp Family -Cannabaceaementioning
confidence: 99%
“…Hop extract has been found to possess various pharmacological properties. For instance, it exhibits antitumor and anti-inflammatory effects, as evidenced by previous studies [179]. Moreover, the extract has been reported to possess antibacterial, anti-collagenase, and antioxidant activity [180].…”
Section: Humulus Lupulus L Hemp Family-cannabaceaementioning
confidence: 64%
“…In dermatology, extracts of H. lupulus have been employed as an antipsoriatic medicine [ 179 ]. Furthermore, they are used in the treatment of skin inflammation diseases of adolescents, and hop cones are taken orally to cure baldness, furunculosis, lichen, and scrofula [ 175 , 180 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Hurth et al (2022) developed lipid-rich creams (oil-in-water (O/W) and a water-in-oil (W/O) emulsions) containing a bitter-acids-enriched CO 2 hop extract (1%, 10 mg/mL), testing them in a randomized placebo-controlled doubleblind UVB erythema study with 40 healthy volunteers, using hydrocortisone acetate (1%) as the positive control. The results demonstrated that only the O/W cream formulations exhibited an in vivo anti-inflammatory effect in the UVB erythema tests, probably due to the presence of penetration enhancers (e.g., propanediol) and the specific chemical profile of the extract in terms of solubility and lipophilicity of the bioactive components present in the galenic formulation tested [160]. Dabrowski et al (2022) conducted a clinical trial on 50 adult patients affected by acute respiratory failure caused by the COVID-19 infection, treating a group with an extract from H. lupulus rich in XN as adjuvant therapy (three times a day every 8 h at a dose of 1.5 mg/kg body weight, for 7 days) [161].…”
Section: Human Studies and Clinical Trial Evidence Of Hopsmentioning
confidence: 98%